Ugnayang Pilipino [soundrecording]. ([Manila] Communications Foundation for Asia [manufacturer])
Designed for Filipinos who are working overseas and filling their spiritual and emotional needs as Filipinos. Each cassette contains a monthly mass, popular Filipino song, laugh-ins, greetings from an actor/actress, inspirational messages from Cardinal Sin and a layman. A blank portion of the tape can be utilized by the overseas worker to deliver special messages in his own voice. It makes the worker feel that he is never really far from home and his love ones.
Keywords: Inspiration -- Religious aspects; Mass -- Celebration; Spiritual life; Filipinos -- Employment -- Foreign countries; Filipinos -- Communication; Sociology; Religion